Pengaruh Rasio Keuangan Terhadap Likuiditas Saham Pada Sektor Perbankan Di Bursa Efek Indonesia Periode 2008-2012 - Esterrina Fermantiningrum; Matsani Matsani (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2019)
The purpose of this research is to examine the Effect of Financial Ratios on Stock Liquidity in the Banking Sector listed in Indonesia Stock Exchange, during 2008-2012. The variables used in this study include stock liquidity (LKS) as the dependent variable with LDR, DER, ROE, PER, PBV, EPS, and ROA as the independent variables. Samples were selected based on the purposive sampling method. Samples in this research come from 26 companies in the banking sector in the period 2008 until 2012 which consist of 130 observations. This research used panel data regression analysis. The PLS (Common), Fixed Effect Model, and Random Effect models were then tested to select the most suitable model. The LM test and Hausman concluded that the Random Effect is the most appropriate model. Hypothesis testing was conducted by using the Adjusted R Square, F test, and T-test based on the Random Effect Model. The results of the research show that DER, PER, PBV, and ROA affect stock liquidity (LKS) while liquidity LDR, ROE, and EPS have no influence on stock liquidity (LKS). The coefficient of determination (Adjusted R Square) indicates that 30.58% of fluctuation in stock liquidity (LKS) can be explained by the seven independent variables namely, LDR, DER, ROE, PER, PBV, EPS, and ROA.